2022
DOI: 10.1093/plphys/kiac337
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive nature of the plant circadian clock in natural environments

Abstract: The plant circadian clock coordinates developmental, physiological, and metabolic processes with diel changes in light and temperature throughout the year. The balance between the persistence and plasticity of the clock in response to predictable and unpredictable environmental changes may be key to the clock’s adaptive nature across temporal and spatial scales. Studies under controlled conditions have uncovered critical signaling pathways involved in light and temperature perception by the clock; however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 117 publications
2
15
0
Order By: Relevance
“…The circadian clock interacts with the predominant external timing cues of light and temperature to partition or phase the expression of almost all genes to specific time of day (TOD) to ensure proper growth and development [ 3 , 4 ]. However, most studies only look at a limited number of lab-based conditions to study the TOD regulation of gene expression, while there is a need to better understand TOD regulation under natural and field conditions over development [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circadian clock interacts with the predominant external timing cues of light and temperature to partition or phase the expression of almost all genes to specific time of day (TOD) to ensure proper growth and development [ 3 , 4 ]. However, most studies only look at a limited number of lab-based conditions to study the TOD regulation of gene expression, while there is a need to better understand TOD regulation under natural and field conditions over development [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants under natural conditions experience changing day length and thermocycles that they must integrate to synchronize with the environment over time [ 3 , 7 ]. Over the year, the day length and solar radiation vary by latitude with the longest and shortest days (solstice) occurring in June and December, respectively, while temperature also varies by magnitude between night and day and overall average highs and lows, yet with a lag in reference to the solstices.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that 1792 SO genes had both seasonal and diurnal oscillations (62.2% of SO genes)(Nagano et al, 2019). Recently, the complex effects of clock genes in the natural environment have received increasing attention (Oravec and Greenham, 2022) because rising temperatures due to global warming disrupt existing plant responses to day length and temperature during seasonal events. Accordingly, we have now established a convenient experimental system using SGCmini.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CBF target CORs, such as COR15A, COR47, KIN1, and RD29A, leads to an increase in plant freezing tolerance 12,15,16 . In addition, cold responsiveness of plants is regulated by circadian clock system, which is involved in plant stress responses through controlling daily energy expenditure and enabling plants to grow and reproduce under seasonal and daily temperature variation [17][18][19][20][21] . In the clock system, some circadian clock-related TFs, such as CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), LATE ELONGATED HYPOCOTYL (LHY), and REVEILLES (RVEs), have been proven involved in cold tolerance by directly regulating the expression of downstream CORs, such as CBFs, COR15A/15B, COR28, and COR27 2,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%